Bedding additives reduce ammonia emission and improve crop N uptake after soil application of solid cattle manure. (1st March 2018) - Shah, Ghulam Abbas; Shah, Ghulam Mustafa; Rashid, Muhammad Imtiaz; Groot, Jeroen C.J.; Traore, Bouba; Lantinga, Egbert A.
Abstract: This study examined the influences of three potential additives, i.e., lava meal, sandy soil top-layer and zeolite (used in animal bedding) amended solid cattle manures on (i) ammonia (NH3 ), dinitrous oxide (N2 O), carbon dioxide (CO2 ) and methane (CH4 ) emissions and (ii) maize crop or grassland apparent N recovery (ANR). Diffusion samplers were installed at 20 cm height on grassland surface to measure the concentrations of NH3 from the manures. A photoacoustic gas monitor was used to quantitate the fluxes of N2 O, CH4 and CO2 after manures' incorporation into the maize-field. Herbage ANR was calculated from dry matter yield and N uptake of three successive harvests, while maize crop ANR was determined at cusp of juvenile stage, outset of grain filling as well as physiological maturity stages. Use of additives decreased the NH3 emission rates by about two-third from the manures applied on grassland surface than control untreated-manure. Total herbage ANR was more than doubled in treated manures and was 25% from manure amended with farm soil, 26% and 28% from zeolite and lava meal, respectively compared to 11% from control manure. In maize experiment, mean N2 O and CO2 emission rates were the highest from the latter treatment but these rates were not differed from zero control in case of manures amended with farm soil or zeolite. However, mean CH4 emissions was not differed among all treatments during the whole measuring period. The highest maize crop ANR was obtained at the beginning of grain filling stage (11–40%), however ample lower crop recoveries (8–14%) were achieved at the final physiological maturity stage. This phenomenon was occurred due to leaf senescence N losses from maize crop during the period of grains filling. The lowest losses were observed from control manure at this stage. Hence, all additives decreased the N losses from animal manure and enhanced crop N uptake thus improved the agro-environmental worth of animal manure. Highlights: Bedding additives effect were tested on GHG emissions and crop yield from soil applied cattle manure. All additives reduced NH3 emission by two-third from manure applied on grassland. N2 O and CO2 emission were the highest in untreated manure incorporated in maize. Crops N recovery from treated manure was ∼2 times higher than untreated manure.